1999
DOI: 10.1038/sj.onc.1202909
|View full text |Cite
|
Sign up to set email alerts
|

The TGF-β signaling inhibitor Smad7 enhances tumorigenicity in pancreatic cancer

Abstract: Transforming growth factor-beta (TGF-b) signaling is dependent on the heterodimerization of the type II TGFb receptor (TbRII) with the type I TGF-b receptor (TbRI). Activated TbRI then mediates TGF-b signals by inducing the phosphorylation of Smad2 and/or Smad3, which separately hetetorodimerize with Smad4 and translocate to the nucleus. Phosphorylation of Smad2/ Smad3 by activated TbRI is inhibited by two newly discovered members of the Smad family, Smad6 and Smad7. We now report that Smad7 mRNA levels are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(179 citation statements)
references
References 52 publications
6
169
1
3
Order By: Relevance
“…The repression of Ihh mRNA by TGF-␤1 in Colo-357 indicates that TGF-␤1 has a potential role in the regulation of Ihh expression in pancreatic cancer. Inasmuch as most pancreatic cancers are resistant to TGF-␤ signaling due to Smad4 mutations, 7 Smad6/7 overexpression, 42,43 or reduced expression of TGF-␤ receptor I, 44 these alterations may result in loss of this repressive effect and then excessive activation of Ihh transcription in pancreatic cancer.…”
Section: Figurementioning
confidence: 99%
“…The repression of Ihh mRNA by TGF-␤1 in Colo-357 indicates that TGF-␤1 has a potential role in the regulation of Ihh expression in pancreatic cancer. Inasmuch as most pancreatic cancers are resistant to TGF-␤ signaling due to Smad4 mutations, 7 Smad6/7 overexpression, 42,43 or reduced expression of TGF-␤ receptor I, 44 these alterations may result in loss of this repressive effect and then excessive activation of Ihh transcription in pancreatic cancer.…”
Section: Figurementioning
confidence: 99%
“…Aliquots of each sample ( 10 l) were then assayed using the MLX microtiter plate luminometer ( Dynex Technologies, Chantilly, VA ) 18, and the Promega assay reagent according to the manufacturers' instructions, as previously reported. 27 Adenoviral infection of L6 cells was carried out with minor modifications. Thus, L6 cells were seeded in 12 -well plates at a density of 25,000 cells /well.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…The role of TGF-b signaling as a tumor suppressor pathway in pancreatic carcinoma is best illustrated by the presence of chromosomal deletions and mutations in DPC4 in 55% of pancreatic tumors (Hahn et al, 1996), a tumor suppressor that has been implicated in mediating the growth inhibitory (Peng et al, 2002) and antiangiogenic (Schwarte-Waldhoff et al, 2000) effects of TGF-b. Fifty percent show an overexpression of the inhibitory Smad7 (Kleeff et al, 1999); moreover, in vivo disruption of TGF-b signaling by Smad7 leads to premalignant ductal lesions in the pancreas (Kuang et al, 2006). Inactivating mutations in both TGFBR1 (Goggins et al, 1998) and TGFBR2 have been observed in pancreatic carcinoma, but are less common than downregulation of ALK5 combined with elevated expression of TbRII (Friess et al, 1993a;Baldwin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%